Algeria : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
In this study, the following statistical data are presented in detail: supply and use of resources at current prices, production, exports, consumption of petroleum products and gas products, land use patterns, crop yields, livestock, production of minerals, consumer price index, income of households, central government revenue, rehabilitation fund operations, housing supply, monetary survey, structure of interest rates, expansion of Bank's network, breakdown of imports and exports, exports of hydrocarbon, trade indices, balance of payments, external debt, nominal and real effective exchange rates, and so on.